SORBENTS BASED ON THE BIOMASS OF THE WORMWOOD-TARRAGON (ARTEMISIA DRACUNCULUS) PLANT FOR WATER PURIFICATION FROM OIL POLLUTANTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
One of the modern priorities in the fjeld of environmental protection is the search for efgective and environmentally friendly wastewater treatment technologies. Purifjcation of water from various pollutants is currently a very urgent task. When choosing a sorbent, they are guided by the sorption capacity for the extracted substances, the effjciency of purifjcation, as well as the cost and availability of the sorbent. Kyrgyzstan has the richest resources of annually renewable plant raw materials, which are still little given importance as sources of chemical and energy raw materials. The use of these materials, which are local raw materials, makes it possible to eliminate large-tonnage agricultural waste.The purpose of the study is to study the sorption properties of sorbents obtained on the basis of the biomass of the wormwood-tarragon (Artemisia dracunculus) plant and to assess the possibility of their use for the purifjcation of oily water, ensuring the environmental safety of the environment.
Keywords: activation, oil pollutants, wastewater treatment, sorbents, sorption capacity.